(3JGQjN GHf HQjGds - (3YHO GdHGbj Hf eMeO Hf HQjGd GdMLGRj, CHh HcQs
(3ChdgG (B:s
(3CNHQfi HJUGfja CHh eMeO Ydi Hf MRe bGd hbQCJ Ydi CHj eMeO Hf YHO Gddg Hf eMeO Hf eQRhb bGd QMeg Gddg JYGdi HGH fSH QShd Gddg Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3cGf SfI EMOi hKdGKjf hKdKeGjI hdGjI GdbGFe ddg YHO Gddg GHf GdbGOQ HGddg Jhdi HYO GdbGOQ HGddg GHh LYaQ YHO Gddg GHf GdbGOQ HGddg agh CejQ GdeDefjf Gdjhe s
(3GdfSNI HgG MhGTs
(3HChdg eWGdYI dYKeGf Hf GdNTGH heMeO Hf GdaNQi HQSe GdNRGfI GdeYehQI GdYGdjI GdehdhjI GdfGUQjI hdOG GdebQ GdeQMhe GbHYG GUs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs